2019
DOI: 10.1101/613638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal network reorganization underlies the formation of a temporal association memory

Abstract: AbstractEpisodic memory requires linking events in time, a function dependent on the hippocampus. In “trace” fear conditioning, animals learn to associate a neutral cue with an aversive stimulus despite their separation in time by a delay period on the order of tens of seconds. But how this temporal association forms remains unclear. Here we use 2-photon calcium imaging to track neural population dynamics over the complete time-course of learning and show that, in contrast to p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…As in Ahmed et al (2020), we discarded any events whose amplitude was below 4 median absolute deviations of the raw trace, and discretized the resulting signal for all subsequent analysis.…”
Section: Neural Data Analysismentioning
confidence: 99%
“…As in Ahmed et al (2020), we discarded any events whose amplitude was below 4 median absolute deviations of the raw trace, and discretized the resulting signal for all subsequent analysis.…”
Section: Neural Data Analysismentioning
confidence: 99%
“…Figure 1C). Furthermore, we simulated variations of the original TUNL task that controlled for (1) the memory demands during the delay period and (2) the temporal structure of the episodes in order to investigate the effects of task demand and task structure on the emergence and informativeness of sequence cells, which had been the subject of discrepancies in rodent studies 8,9,26 . We found that sequence cells emerged across task demands and task structures (Figure 3B, 4B).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on rodent hippocampal time cells has led to disputes on whether these sequential activity patterns indeed contribute to stimulus-encoding in memory, or are merely an artifact 8,9,26 . Here, we addressed these discrepancies and investigated the effect of task demand on temporal representations by developing a non-mnemonic version of the TUNL task (NoMem TUNL) wherein, during the choice phase, the agent may choose either the match or the nonmatch location to receive a reward, thus eliminating the demand for the agent to remember the sample location across the delay period (Figure 3A).…”
Section: The Emergence Of Stimulus-encoding Sequences Depends On Cognitive Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…end, some argue that hippocampal ensembles are flexible in regard to the content of their inputs and, consequently, will ordinally map any feature space (though one should consider that dense innervation of the hippocampus from regions carrying head direction (HD) information may bias the system to respond to the spatial domain in rodents). An important question may be if there is any continuous feature of the task space that would not be reliably mapped by hippocampal sequences (Ahmed et al, 2020;Aronov et al, 2017). Time cell responses have been shown in a wide range of different structures, including hippocampal region CA1 (Kraus et al, 2013;Mau et al, 2018;Pastalkova et al, 2008), hippocampal region CA3 (Salz et al, 2016), and the entorhinal cortex (Heys and Dombeck, 2018;Kraus et al, 2015;Tsao et al, 2018).…”
Section: Coding Of Time (Time Cells)mentioning
confidence: 99%